2017
DOI: 10.1051/0004-6361/201629314
|View full text |Cite
|
Sign up to set email alerts
|

A polarimetric investigation of Jupiter: Disk-resolved imaging polarimetry and spectropolarimetry

Abstract: Context. Polarimetry is a powerful remote sensing tool to characterise solar system planets and, potentially, to detect and characterise exoplanets. The linear polarisation of a planet as a function of wavelength and phase angle is sensitive to the cloud and haze particle properties in planetary atmospheres, as well as to their altitudes and optical thicknesses. Aims. We present for the first time polarimetric signals of Jupiter mapped over the entire disk, showing features such as contrasts between the belts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(73 reference statements)
2
13
0
Order By: Relevance
“…Observations of individual objects have shown that for Rayleigh scattering atmospheres like Uranus and Neptune (Schmid et al 2006b) the fractional polarization can be substantially higher than this value (p(90 • ) > 20 %). For mostly haze scattering atmospheres as found on Titan (Tomasko & Smith 1982;Bazzon et al 2014) or in the polar regions of Jupiter (Smith & Tomasko 1984;Schmid et al 2011;McLean et al 2017) the fractional polarization can even reach values up to p(90 • ) ≈ 50 %. On the other hand, the Mie scattering process in the clouds that dominate the atmospheres of Venus, Saturn or the equatorial regions of Jupiter produces a lower polarization in the visual wavelengths < 10 % (Smith & Tomasko 1984;Hansen & Hovenier 1974).…”
Section: The Polarization Of the Reflected Light From Planetsmentioning
confidence: 96%
“…Observations of individual objects have shown that for Rayleigh scattering atmospheres like Uranus and Neptune (Schmid et al 2006b) the fractional polarization can be substantially higher than this value (p(90 • ) > 20 %). For mostly haze scattering atmospheres as found on Titan (Tomasko & Smith 1982;Bazzon et al 2014) or in the polar regions of Jupiter (Smith & Tomasko 1984;Schmid et al 2011;McLean et al 2017) the fractional polarization can even reach values up to p(90 • ) ≈ 50 %. On the other hand, the Mie scattering process in the clouds that dominate the atmospheres of Venus, Saturn or the equatorial regions of Jupiter produces a lower polarization in the visual wavelengths < 10 % (Smith & Tomasko 1984;Hansen & Hovenier 1974).…”
Section: The Polarization Of the Reflected Light From Planetsmentioning
confidence: 96%
“…The q(θ pp ) = q(θ, 0 • : 180 • ) curve shows a weakly negative section around the back-scattering directions θ pp = 50 • −80 • . This is a well-known higher order scattering effect (e.g., van de Hulst 1980), which for dust (or haze) scattering in Jupiter and Titan leads to strong "negative" limb polarization effects (Schmid et al 2011;McLean et al 2017;Bazzon et al 2014).…”
Section: Calculations For a Plane Parallel Surfacementioning
confidence: 97%
“…There are relatively few imaging polarimetry observations of Jupiter in the literature (e.g. Schmid et al 2011;McLean et al 2017) and these have limited coverage in wavelength and phase angle. The ability to obtain wide wavelength coverage, high quality polarimetry with a small easily accessible telescope makes possible extensive studies of the phase angle dependence of the polarization structure, which provides information on cloud particle sizes and composition.…”
Section: Solar System Sciencementioning
confidence: 99%